2010
DOI: 10.1128/aem.01976-10
|View full text |Cite
|
Sign up to set email alerts
|

Promising Immunomodulatory Effects of Selected Strains of Dairy Propionibacteria as Evidenced In Vitro and In Vivo

Abstract: Immunomodulatory properties of 10 dairy propionibacteria, analyzed on human peripheral blood mononuclear cells (PBMCs), revealed a highly strain-dependent induction of anti-inflammatory cytokine interleukin 10 (IL-10). Two selected strains of Propionibacterium freudenreichii showed a protective effect against two models of colitis in mice, suggesting a probiotic potential predicted by immune-based selection criteria for these cheese starter bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
87
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 33 publications
8
87
0
Order By: Relevance
“…Other dairy P. freudenreichii strains also showed promising immunomodulatory properties by strongly inducing the synthesis of anti-inflammatory IL-10 by human PBMCs and could be helpful in the treatment of inflammatory conditions or diseases [171].…”
Section: Dairy Propionibacteria: Less Conventional Probiotics To Imprmentioning
confidence: 99%
See 2 more Smart Citations
“…Other dairy P. freudenreichii strains also showed promising immunomodulatory properties by strongly inducing the synthesis of anti-inflammatory IL-10 by human PBMCs and could be helpful in the treatment of inflammatory conditions or diseases [171].…”
Section: Dairy Propionibacteria: Less Conventional Probiotics To Imprmentioning
confidence: 99%
“…It has been demonstrated that consumption of either isolated BGS or P. freudenreichii strains ameliorate experimental colitis in mice and human ulcerative colitis [171,[189][190][191][192]. The mechanism proposed for this effect was restoring of microbiota intestinal balance and suppressing inflammatory lymphocyte infiltration.…”
Section: Alleviation Of Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…lactis (Santos-Rocha et al, 2012), as well as Lactobacillus helveticus (Guglielmetti et al, 2010). Modulation of colon cancer cell growth was also reported in vitro and/or in animal models for P. freudenreichii (Cousin et al, 2010;Lan et al, 2008), when the cells were exposed to yogurt containing S. thermophilus and L. bulgaricus (Narushima et al, 2010;Perdigon et al, 2002) and L. helveticus (de Moreno et al, 2010). Future trends may thus include the development of specific fermented dairy products designed for specific population.…”
Section: Concluding Remarks and Future Trendsmentioning
confidence: 85%
“…For example, immunomodulatory anti-inflammatory properties were described in certain strains of Propionibacterium freudenreichii (Foligné et al, 2010;Deutsch et al, 2012), Streptococcus thermophilus (Ogita et al, 2011), Lactobacillus delbrueckii subsp. bulgaricus and subsp.…”
Section: Concluding Remarks and Future Trendsmentioning
confidence: 99%